O Conselho de Estado Imperial e a política externa brasileira : as relações com os países platinos (1851-1870) - Silva, Jaqueline Schmitt da (2014)
This work seeks to understand the council of State of Brazil Empire and its performance in external Brazilian politics for platinum region in the period 1851, marked the beginning of the interventions in the region of Brazil, until 1870, the date that marks the end of the Paraguayan war. During the reign of Dom Pedro II, was present on the political path the third State Council, approved by law in 1842 and remained in force until the end of the Empire, the Emperor should advise on the most varied subjects, mainly on the war declaration, adjustments of peace, negotiations with foreign nations, as well as on all occasions when the Emperor resolved using the attributions of moderating power. Formed by the most important politicians of the time, were selected and appointed by the Emperor. Before coming to the State Council passed several positions in the public administration, as chairmen of the Council of Ministers, Senators, State s Ministers, Province s Presidents, gentlemen, composing a picture of men also called because of their track record and experience in politics. For the study are utilized Proceedings of the Section of Foreign Affairs of the State Council, and the Acts of the Council of State Full, noting those that specifically address the relationship between Brazil and neighboring of Prata: Argentina, Uruguay and Paraguay. During this period, marked by constant conflicts and intense activity of Brazilian diplomacy in the region, the State Council played an important role in discussions of foreign politics to be developed with respect to these countries. Analyzing the minutes of meetings, it is observed that though if they were complex diplomatic relations and the opinions within the Council of State were in many different occasions, the conclusions arrived prioritized wide defending the interests of the Empire in the region, aimed at strengthening the sovereignty of Brazil on the other countries and its consolidation as a hegemonic nation among the countries of South America